Experimental and Numerical Study of Shock Absorber Characterization and The Implication on The Dynamics of Half Vehicle Suspension System Model - An-Nizhami, Avicenna; Sriyanto, Nanang Budi; Sumiyarso, Bambang; Ulum, Showi Nailul; Riadini, Elfrida Rizky; Widodo, Ignatius Gunawan (Jurnal Rekayasa Mesin, 2023)
This study aimed to characterized shock absorber damping for passenger comfort. The riding comfort of the vehicle has direct correlation to the damping characteristic of the shock absorber of the suspension system. Two different shock absorbers were experimentally evaluated, and their damping characteristics were integrated into a half-car model to study the vehicle's dynamic response to harmonic road disturbances. The investigation involved numerical simulations of the half-car model subjected to harmonic road disturbances, represented by a set of ordinary differential equations solved using the Dormand-Prince method. Experimental data yielded average damping forces of 502.77 N for shock-absorber #1 and 192.03 N for shock-absorber #2. Calculations resulted in damping coefficients of 3888.57 N ·s/m for shock-absorber #1 and 1397.85 N ·s/m for shock-absorber #2, with corresponding damping ratios of 0.29 and 0.105. These damping ratios generally aligned with typical values for passenger car shock absorbers, except for shock-absorber #2, which deviated from the expected range. The study found that at 60 km/h and 90 km/h, shock-absorber #1 with Î¶=0.29 exhibited superior performance in reducing displacement amplitude compared to shock-absorber #2 at Î¶=0.105. However, at 120 km/h, both shock-absorbers displayed similar responses, with shock-absorber #1 slightly surpassing shock-absorber #2 in displacement amplitude.